Gut Microbiome in Obsessive Compulsive Disorder: Potential of Probiotics as an Adjuvant Therapy - Grace Yong-En Kong; Vengadesh Letchumanan; Loh Teng-Hern Tan; Jodi Woan-Fei Law (Progress in Microbes and Molecular Biology)
The gut-brain axis concept has become an exciting area of research in psychiatry. Gastrointestinal inflammation and gut microbiome dysbiosis have been associated with mental health disorders. Obsessive-compulsive disorder (OCD) is a debilitating and complex mental illness that cannot be completely curable, stemming from many causes and risk factors. Generally, there is limited research on OCD and its association with the gut microbiome compared to other psychiatric conditions such as depression and anxiety. This review aims to provide insights into the association of gut microbiome and gastrointestinal inflammation with OCD. Besides, the role of probiotics as a potential therapy will be discussed in this review. The studies compiled in this review demonstrated variations in the gut microbial composition, often with lower microbial diversity in OCD patients compared to the controls. The gut microbiome is also involved in regulating the immune system. Alteration in certain groups of gut bacteria could give rise to inflammation and manifestations of gastrointestinal symptoms in OCD patients. As an approach to restoring the balance of the gut microbiome, probiotics serve as an effective solution. In vivo animal studies showed that probiotics can potentially improve OCD symptoms. Nevertheless, clinical trials are required to determine the efficacy of probiotics as an adjuvant therapy to alleviate OCD symptoms.